Electrochemical Sandwich Immunoassay for the Ultrasensitive Detection of Human MUC1 Cancer Biomarker. (22nd December 2013) - Taleat, Zahra; Cristea, Cecilia; Marrazza, Giovanna; Săndulescu, Robert
Abstract : A new electrochemical sandwich immunoassay for the ultrasensitive detection of human MUC1 cancer biomarker using protein G-functionalized magnetic beads (MBs) and graphite-based screen-printed electrodes (SPEs) was developed. Magnetic beads were employed as the platforms for the immobilization and immunoreaction process. A pair of primary and secondary antibodies was used to capture the MUC1 protein. After labeling with a third antibody conjugated with horseradish peroxidase (HRP), the resulting conjugate was trapped at the surface of the graphite-based SPEs and MUC1 determination was carried out by differential pulse voltammetry (DPV) at 0.4 V upon H2 O2 addition using acetaminophen (APAP) as the redox mediator. A linear relationship was obtained for the detection of human MUC1 over a range of 0–25 ppb with the lowest detection limit of 1.34 ppb when HRP was applied as a label. Preliminary experiments were performed using disposable electrochemical sensors in order to optimize some parameters (i.e., incubation times, concentrations, and blocking agent).